Single Subject Research: Implementasi Pembelajaran Problem Posing terhadap Kemampuan Berpikir Kreatif Siswa Field Dependent - Ilham Rais Arvianto; Merarinta Ginting (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
This study aims to analyze the process and describe the results of problem posing learning treatments on students' creative thinking skills field dependent on statistical material. This research is categorized as Single Subject Research (SSR) A-B research with a quantitative approach. The study was designed for 8 sessions with 4 initial sessions of the baseline phase and 4 final sessions of the intervention phase (problem posing learning). Research sample were selected using purposive sampling technique. Collecting data using GEFT, problem submission test (TPM), observation, and interviews. Research data were analyzed in 2 ways, i.e. analysis under and between conditions. The results showed that students with field dependent cognitive style could pose problems in statistical material by using a problem posing learning model. The results of the evaluation before and after treatment showed an increase in the components of creative thinking, fluency and novelty, so that the treatment given could improve the mathematical creative thinking skills of field dependent students. However, the creative component of novelty cannot yet be improved